Extracellular Nanovesicles: From Intercellular Messengers to Efficient Drug Delivery Systems - Deshmukh, Sachin Kumar (ACS Omega, 2021)
[Image: see text] Nanosized extracellular vesicles (nEV) are released by all the eukaryotic cells into the extracellular spaces. They serve as crucial mediators of intercellular communication, and their presence has been detected in a variety of body fluids. nEV carry nucleic acids, lipids, proteins, and metabolites from the donor cells and transfer them to the recipient cells in the vicinity or distant locations to cause changes in their biological phenotypes. This very property of nEV makes them a suitable carrier of the drugs for therapeutic applications. The use of nEV as a drug delivery system offers several advantages over synthetic nanoparticles, including biocompatibility, natural targeting ability, and long-term safety. Further, nEV can be isolated from various biological sources, quickly loaded with the drug of choice, and modified to further enhance their utility as targeted drug delivery vehicles. Here we review these aspects of nEV and discuss the parameters that should be kept in mind while choosing the nEV source, drug loading method, and surface modification strategies. We also discuss the challenges associated with the nEV-based drug delivery platforms that must be overcome before realizing their full potential in clinical applications.